Accuracy of an autocalibrated pulse contour analysis in cardiac surgery patients: a bi-center clinical trial. Issue 1 (December 2015) - Broch, Ole; Carbonell, Jose; Ferrando, Carlos; Metzner, Malte; Carstens, Arne; Albrecht, Martin; Gruenewald, Matthias; Höcker, Jan; Soro, Marina; Steinfath, Markus; Renner, Jochen; Bein, Berthold
Abstract Background Less-invasive and easy to install monitoring systems for continuous estimation of cardiac index (CI) have gained increasing interest, especially in cardiac surgery patients who often exhibit abrupt haemodynamic changes. The aim of the present study was to compare the accuracy of CI by a new semi-invasive monitoring system with transpulmonary thermodilution before and after cardiopulmonary bypass (CPB). Methods Sixty-five patients (41 Germany, 24 Spain) scheduled for elective coronary surgery were studied before and after CPB, respectively. Measurements included CI obtained by transpulmonary thermodilution (CITPTD ) and autocalibrated semi-invasive pulse contour analysis (CIPFX ). Percentage changes of CI were also calculated. Results There was only a poor correlation between CITPTD and CIPFX both before (r 2  = 0.34, p  < 0.0001) and after (r 2  = 0.31, p  < 0.0001) CPB, with a percentage error (PE) of 62 and 49 %, respectively. Four quadrant plots revealed a concordance rate over 90 % indicating an acceptable correlation of trends between CITPTD and CIPFX before (concordance: 93 %) and after (concordance: 94 %) CPB. In contrast, polar plot analysis showed poor trending before and an acceptable trending ability of changes in CI after CPB. Conclusions Semi-invasive CI by autocalibrated pulse contour analysis showed a poor ability to estimate CI compared with transpulmonary thermodilution. Furthermore, the new semi-invasive device revealed an acceptable trending ability for haemodynamic changes only after CPB. Trial registration ClinicalTrials.gov:NCT02312505 Date: 12.03.2012